Reconstruction of The North Nias Giri-Giri Dance: A Creative Process - Tuti Rahayu; Yusnizar Heniwaty; Wiflihani (Mudra Jurnal Seni Budaya, 2024)
This research aims to find out the views of the people of Lahewa Village, North Nias Regency, regarding the Giri-giri dance which has been lost; the process of reconstructing the Giri-giri dance; the results of the reconstruction of the Giri-giri dance; and the creative process in its reconstruction. This research process resulted in a video and book on the Giri-giri dance from the local culture of North Nias. The method used in this research is qualitative in the form of descriptive analysis. The scope of the discussion includes the following: 1) What is the process of reconstructing the Giri-giri dance? 2) What is the shape of the reconstruction of the Giri-giri dance? 3) What factors support the reconstruction of the Giri-giri dance? Data analysis was carried out from each part found. Data was obtained from literature study, observation, and interviews. The research locations were carried out in the cities of Medan and Nias. The data that has been collected is analyzed using a qualitative paradigm using project-based research. The concept used in reconstructing the Giri-giri dance is structuring forms so that changes can be seen in the movement components, make-up and clothing, floor design, and dance props by providing innovative tourism art concepts, namely short, concise, engaging, and selling value. So, based on this concept, the Giri-giri dance can become a performing arts asset in North Nias Regency and Medan City.